Disrupting the deficit discourse: reframing metaphors for professional learning in the context of appreciative inquiry. Issue 1 (1st January 2019) - Scott, John Trevitt; Armstrong, Ann Cheryl
Abstract: This paper originates from an earlier comparative study of professional learning in a Christian, a Jewish, and a Muslim Australian independent school, in which teachers and school leaders were asked to engage in critical reflection as to the school's distinctive characteristics. The paper recognizes the tension that may arise in all schools from the pressure to devote their professional learning programs to meeting mandated government requirements. This pressure may include meeting the requirements of a standards-based framework to demonstrate the acquisition of appropriate skills and knowledge. Rather than understanding professional learning as focused largely on responding to perceived deficits in skills and knowledge, we critique our previously used methodology and argue for the formulation of metaphors for professional learning within an Appreciative Inquiry perspective as a strategy to disrupt the discourse of deficit, replacing it with one of growth and self-determined change. This methodological approach is presented as being helpful for all schools (faith-based and secular). A suggested interview schedule illustrates how this methodology might be put into practice.